A low-calorie diet raises β-aminoisobutyric acid in relation to glucose regulation and leptin independent of exercise in women with obesity - Faiz, Habiba; Malin, Steven K. (Frontiers in Physiology, 2023)
β-aminoisobutyric acid (BAIBA) is a suggested cytokine secreted from skeletal muscles that regulates insulin sensitivity, pancreatic function, and fat oxidation. However, no studies to date have examined if a low-calorie diet (LCD) or LCD+interval exercise (LCD+INT) differentially raises BAIBA. The purpose was to examine if LCD or LCD+INT raises circulating BAIBA in relation to cardiometabolic health. For this, twenty-three women with obesity were randomized to either 2-weeks of LCD (n=12, 48.4±2.5y, 37.84±1.5kg/m2; ~1200kcal/day) or LCD+INT (n=11, 47.6±4.3y, 37.9±2.3kg/m2; ~60min/d of INT alternating 3 min of 90% and 50% HRpeak), with matched energy availability. Fasting BAIBA and adipokines whereas glucose, insulin, C-peptide, and FFA were obtained after every 30 min up to 120 min during a 75g OGTT to estimate total area under the curve (tAUC), insulin sensitivity (SIIS), pancreatic function (disposition index (DI)), and hepatic insulin clearance (HIC). Fuel use (indirect calorimetry) was tested at 0, 60, and 120 min of the OGTT along with fitness (VO2peak) and body composition (BodPod). Both treatments lowered body weight (P<0.001) and leptin (P<0.001) but raised BAIBA (P=0.007) and insulin sensitivity (P=0.02). LCD+INT increased VO2peak (P=0.02) and REE tAUC120min (P=0.02) while LCD and LCD+INT decreased carbohydrate oxidation (CHOox) tAUC120min (P<0.001). Increased BAIBA associated with reduced weight (r=-0.67, P<0.001), leptin (r=-0.66, P=0.001), CHOox tAUC120min (r=-0.44, P=0.03) and DImuscle120min (r=-0.45, P=0.03), but elevated HIC120min (r=0.47, P=0.02). Concluding, LCD and LCD+INT increased BAIBA in relation to reduced body weight and pancreatic function in women with obesity. This suggests energy deficit is a key factor regulating circulating BAIBA.